Persepsi Apoteker dan Pengetahuan Apoteker Dalam Manajemen Farmasi Terhadap Pelayanan Kefarmasian Secara Online Pada Apotek Di Kota Medan - Panjaitan, Magdalena; Wiryanto, Wiryanto; Khairunnisa, Khairunnisa (Journal of Pharmaceutical and Sciences, 2026)
Digital transformation is driving significant changes in pharmaceutical services, including the utilization of online drug consultation and sales services. This study aims to analyze the influence of pharmacists' perceptions and knowledge on online pharmaceutical services and to strengthen quantitative findings thru qualitative results. The method used was a nested mixed method sequential explanatory approach, with the initial stage involving a survey of 200 pharmacists, followed by in-depth interviews with 20 informants consisting of 10 pharmacists who had been providing online pharmaceutical services for more than 3 years and 10 pharmacists who had not yet provided online pharmaceutical services but had more than 3 years of work experience as pharmacists. The data analysis results show that perception significantly influences online pharmacy services (p < 0.001), as does knowledge (p < 0.001). A coefficient of determination of 42.6% (0.426) indicates the significant role of both variables. The interview results with the sources explain the data analysis findings: pharmacists emphasize the importance of technological readiness, regulatory compliance, clear SOPs, and digital competency development as requirements for implementing online pharmaceutical services. This research confirms that strengthening the capacity of pharmacists and the pharmaceutical management system is the foundation for the successful transformation of digital pharmacy services in community pharmacies. This study concludes that pharmacists' perceptions and knowledge significantly influence the quality of online pharmaceutical services. The results of interviews with sources explain the data analysis, showing that technological readiness, regulatory compliance, and pharmacists' digital competence are the main foundations for the successful implementation of online pharmaceutical services in community pharmacies.